Fabrication of ultra-low-cost pure Ti by selective laser melting using the mixed powders of hydride-dehydride titanium powders treated by ball milling and spherical powders. (1st January 2021) - Yang, Xin; Zhang, Zhaoyang; Gu, Wenping; Wang, Ben; Fan, Yazhuo; Miao, Qingdong; Zhao, Sanchao; Xie, Bo
ABSTRACT: Selective laser melting (SLM) currently uses the micro-fine spherical powder prepared by gas atomisation as a raw material. However, the spherical powder is expensive. In order to reduce the cost, this study first ball mills the pure titanium (CP-Ti) powder of hydrogenation-dehydrogenation (HDH). At a high speed and within a short period, the particle size distribution of the powder at a high rotation speed for 15 min is 12–45 μm with an angle of repose 34.3°. Then, the ball milling of titanium was mixed spherical powder with a wide grain size range up to 100 μm. This study presents the results of using SLM to produce CP-Ti parts starting from powder with mixed powder, in a different ratio between modified powder and spherical powder. The ultimate tensile strength (UTS) of SLM-parts of 8:2 ratio has been improved to 507 MPa, and the UTS of parts of 7:3 ratio has been improved to 522 MPa.